PENGARUH KONSTRUKSI REGULASI DESENTRALISASI ASIMETRIS DALAM MEMPERKUAT OTONOMI DAERAH DI SUMATERA BARAT - Putra, Ridwan; Henrizoni, Henrizoni; Putra, Egip Satria Eka; Suryanti, Rini; Sari, Hilda Elsa (Ensiklopedia of Journal, 2025)
This study examines the impact of asymmetric decentralization regulations on the implementation of regional autonomy in West Sumatera Province. Asymmetric decentralization refers to the granting of differentiated authority to specific regions based on their unique historical, social, and cultural characteristics. West Sumatera, with its indigenous nagari-based governance system rooted in customary law and local democracy, emerges as a strong candidate for special region status. Employing a normative juridical approach, this research analyzes relevant legislation and legal doctrines through the lens of decentralization theory. Findings indicate that the asymmetric decentralization model has contributed positively to the preservation of local values and the strengthening of governance based on indigenous wisdom. However, several challenges persist, including fiscal dependency, overlapping policies between central and regional governments, and weak institutional synergy. Therefore, policy harmonization and local capacity strengthening are essential to realizing effective and sustainable regional autonomy in West Sumatera.Keywords: Asymmetric decentralization, regional autonomy, West Sumatera, regulation